2021
DOI: 10.1039/d0ob02225j
|View full text |Cite
|
Sign up to set email alerts
|

Carbazole-modified thiazolo[3,2-c][1,3,5,2]oxadiazaborinines exhibiting aggregation-induced emission and mechanofluorochromism

Abstract: Two novel AIE-active donor–acceptor organoboron complexes with a carbazole donor unit are developed and their morphology-dependent solid-state fluorescence properties are established.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 61 publications
0
12
0
Order By: Relevance
“…Starting materials -4-(9H-carbazol-9-yl)benzoic acid ( 5) and 4- (3,6-di-tert-butyl-9H-carbazol-9-yl)benzoic acid ( 6) -were synthesized as described in our previous work. [17] Acids 5 and 6 were treated with thionyl chloride in hot dry toluene giving corresponding chlorides 7 and 8, which were immediately introduced into reaction with benzo [d]thiazole-2-amine (9) in the presence of triethylamine and catalytic amount of 4-dimethylaminopyridine (DMAP). Amides 10 and 11 were isolated with good yields (72 and 66 %, respectively) after two steps.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Starting materials -4-(9H-carbazol-9-yl)benzoic acid ( 5) and 4- (3,6-di-tert-butyl-9H-carbazol-9-yl)benzoic acid ( 6) -were synthesized as described in our previous work. [17] Acids 5 and 6 were treated with thionyl chloride in hot dry toluene giving corresponding chlorides 7 and 8, which were immediately introduced into reaction with benzo [d]thiazole-2-amine (9) in the presence of triethylamine and catalytic amount of 4-dimethylaminopyridine (DMAP). Amides 10 and 11 were isolated with good yields (72 and 66 %, respectively) after two steps.…”
Section: Resultsmentioning
confidence: 99%
“…These parameters indicate the remarkable thermal stability of both compounds, which is even higher than those of analogues 1 and 2 (T d = 313 and 316°C, respectively). [17] DSC experiments showed that during heating and cooling first cycle, organoboron complex 3 demonstrated single melting and crystallization peaks at 263 and 168°C, respectively. The second heating demonstrate almost not-changed melting peak (258°C) (Figure S2 in the ESI).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations